Laminated Dental Machining Resin Blanks

JP7640044B2Active Publication Date: 2025-03-05TOKUYAMA DENTAL CORP
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2021043493
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-03-17
Publication Date
2025-03-05
Estimated Expiration
2041-03-17

AI Technical Summary

Benefits of technology

【0015】 本発明のブランクは、歯頸部から切端部にかけて滑らかなグラデーションとなっている様子を高度に表現できるようになる。しかも、色調移行層となる中間層は1層だけでよく、さらに顔料や染料を用いた色調調整を必要としない。また、中間層の両端に配置される第一層及び第二で、異なる“切端部色系統の色と歯頚部色系統の色との組み合わせ”を採用した場合でも、中間層を変更する必要は無い。そのため、特許文献3に開示された方法のように3層間の色度差や透明性差を高度に調整して積層する場合と比べて、汎用性と生産性が優れている。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007640044000001
    Figure 0007640044000001
  • Figure 0007640044000002
    Figure 0007640044000002
  • Figure 0007640044000003
    Figure 0007640044000003
Patent Text Reader

Abstract

To provide a resin based blank for lamination type dental cutting processing, capable of reducing change of a color tone from the vicinity of a tooth neck to a cut end part, in an excellent method in productivity.SOLUTION: A cutting processing part of a resin based blank for dental cutting processing, is configured into a multilayer structure formed of three layers, which comprises, between first and second layers formed of a blended pigment or the like and formed of a colored hybrid resin, an intermediate layer which substantially includes no pigment and which exhibits a structure color of a specific color tone without depending on a light incident angle, for adapting to the color tone in the surrounding, the intermediate layer being formed of a structure color-based hybrid resin. A thickness of the intermediate layer is in a range of 0.1-3 mm, and when a color difference being a color difference between layers, is exhibited, a color difference between the first and second layers is 2-30, a color difference between the first and intermediate layers is 2-25, and a color difference between the second and intermediate layers is 5-30, by adjustment.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a laminated type dental mill blank for cutting, having a cutting portion made of a laminate in which a plurality of resin-based material layers are laminated. [Background technology]

[0002] In dental treatment, the use of digital technology is progressing in the manufacture of dental restorations (or dental prostheses) such as inlays, onlays, crowns, bridges, and implant superstructures. For example, as disclosed in Patent Document 1, a CAD / CAM system is becoming more and more popular, which uses a CAD / CAM device based on computer-aided design (CAD) and computer-aided manufacturing (CAM) technology to cut a dental blank for machining made of a nonmetallic material to form a dental restoration from an image of the oral cavity. Here, the dental blank for machining means a cut object (also called a mill blank) that can be attached to a cutting machine in a CAD / CAM system, and generally known examples include a (solid) block formed into a rectangular or cylindrical shape, or a (solid) disk formed into a plate or plate shape. In addition, a holding pin for fixing the dental blank for machining to the cutting machine is often joined to the dental blank for machining, and in such a form, the one integrated with the holding pin is sometimes called a dental blank for machining. In the present invention, the dental blank includes the above-mentioned embodiment integrated with the retaining pin. The main body of the workpiece (the dental blank) is sometimes called the part to be cut.

[0003] As the material to be machined of the dental machining blank, various materials such as glass ceramics, zirconia, titanium, resin, etc. Among these, resin-based materials (also called hybrid resins) consisting of a hardened product of a hardening composition containing an inorganic filler such as silica, a polymerizable monomer such as methacrylate resin, and a polymerization initiator, are attracting attention due to their high workability (machinability), high aesthetics, strength, etc.

[0004] In dental treatment, it is required to give an appearance as close as possible to the color tone of natural teeth. In order to meet such aesthetic requirements, various pigment and dye substances have been added in varying types and amounts to adjust the color tone of the single component of a single-layered resin blank for dental cutting, as well as a multi-layered resin blank for dental cutting made by laminating components of different colors.

[0005] For example, Patent Document 2 proposes a dental CAD / CAM resin block in which a dentin restorative resin layer and an enamel restorative resin layer are laminated as a dental cutting resin blank that is highly versatile and productive and has a high reproducibility of the aesthetic appearance of natural teeth, and at least the dentin restorative resin layer contains light diffusing particles and has a specific diffusion ratio. Patent Document 3 also proposes a dental mill blank that can provide a dental prosthesis having a color tone and transparency more similar to that of natural teeth by cutting, and the laminate includes at least three layers, a top layer, at least one intermediate layer, and a bottom layer, each layer constituting the laminate includes a filler (A) and a polymer (B), the filler (A) of each layer includes at least one type of inorganic particle (a) and at least one type of pigment (C), and the chromaticity difference ΔE between the top layer and the bottom layer is 100 μm. * T is 5.0 or more and 15.0 or less, and the transparency difference ΔΔL between the uppermost layer and the lowermost layer is * T is 5.0 or more and 15.0 or less, and the chromaticity difference ΔE * is 1.0 or more and 5.5 or less, and the transparency difference ΔΔL of all adjacent layers is *is 1.0 or more and 5.0 or less, and the transparency ΔL of the top layer * H is 13.5 or more and 25.0 or less, and the transparency ΔL* of the bottom layer L is 7.0 or more and 13.0 or less, and a dental mill blank has been proposed.

[0006] In addition, in a resin-based blank for dental cutting with a single-layer structure, there are also known ones that can achieve color harmony with natural teeth without using pigments or the like by exhibiting so-called structural color. That is, Patent Document 4 discloses "a resin-based block for dental cutting containing a resin matrix (A) and spherical fillers (B) with an average particle diameter in the range of 230 nm to 1000 nm, wherein 90% or more of the individual particles constituting the spherical fillers (B) are present within the range of 5% before and after the average particle diameter, and the measured color values in the Munsell color system of the colored light under a black background and a white background measured using a color difference meter at a thickness of 10 mm have a lightness (V) of less than 5.0 and a chroma (C) of less than 2.0, and the measured color values in the Munsell color system of the colored light under a black background measured using a color difference meter at a thickness of 1 mm have a lightness (V) of less than 5.0, a chroma (C) of 0.05 or more, and the measured color values in the Munsell color system of the colored light under a white background have a lightness (V) of 6.0 or more and a chroma (C) of less than 2.0. A resin-based block for dental cutting is characterized by this." And according to Patent Document 4, in the above resin-based block for dental cutting, 90% or more of the individual particles constituting the spherical fillers (B) are present within the range of 5% before and after the average particle diameter, and when the refractive index of the resin matrix (A) at 25°C is nP and the refractive index of the spherical fillers (B) at 25°C is nF, the resin matrix (A) and the spherical fillers (B) satisfy the condition of nP < nF. Thus, depending on the particle size of the spherical fillers (B), colored light of a specific color tone is expressed as structural color, and under a black background, it is clearly confirmed as a unique reflection spectrum corresponding to the colored light. However, under a white background, it shows a substantially uniform reflectance over a substantial entire range of the visible spectrum, and the light in the visible spectrum is not confirmed. It is described that it exhibits an effect of widely harmonizing with various surrounding environments.

[0007] In addition, it is known that a composite material in which inorganic particles are dispersed in a resin matrix, which corresponds to the hybrid resin that is the cutting portion of the above-mentioned dental cutting resin block shown in Patent Document 4, will produce a structural color of a constant tone that is not affected by changes in the angle of incidence of light when the shape and particle size distribution of the inorganic particles, the relationship between the refractive index of the inorganic particles and the refractive index of the resin matrix, and the dispersion state of the inorganic particles satisfy certain conditions (see Patent Document 5). [Prior art documents] [Patent documents]

[0008] [Patent Document 1] Special Publication No. 2016-535610 [Patent Document 2] JP 2017-213394 A [Patent Document 3] International Publication No. 2018 / 074605 [Patent Document 4] International Publication No. 2019 / 189698 Brochure [Patent Document 5] Patent No. 6732257 Summary of the Invention [Problem to be solved by the invention]

[0009] Natural teeth are opaque and reddish yellow in the cervical area, gradually changing to a white transparent color toward the incisal edge. Not only are the incisal and cervical areas of natural teeth significantly different in color, but the overall color tone (sometimes called shade) of natural teeth varies from person to person. Therefore, in order to highly express the color tone of natural teeth, it is necessary to prepare a multi-layered mill blank (also called a multi-layered mill blank) for each shade that reproduces the color change from the cervical area to the incisal edge. Also, it is possible to express a smooth color transition by mixing intermediate layers of different colors for each shade so that the color transitions from the cervical area to the incisal edge, and by increasing the number of layers, but producing intermediate layers of multiple colors for each shade requires a lot of manufacturing effort.

[0010] Therefore, an object of the present invention is to provide a resin-based blank for dental cutting that allows a smooth color transition from the color of the cervical portion to the color of the incisal portion and has high productivity. [Means for solving the problem]

[0011] That is, one embodiment of the present invention is a resin-based blank for dental cutting having a cutting part made of a composite material in which inorganic particles are dispersed in a resin matrix, the cutting part having a multi-layer structure including a first layer, a second layer, and an intermediate layer interposed between these layers, and before forming the first layer, the second layer, and the intermediate layer, Note When the composite materials are a first composite material, a second composite material, and an intermediate composite material, respectively, the first composite material and the second composite material contain a pigment and / or a dye and have predetermined color tones different from each other, When the average value and number-based particle size distribution of 30 or more primary particles observed within a single visual field of a photograph of an aggregate of inorganic particles taken with a scanning electron microscope are defined as the average primary particle size and number-based particle size distribution of the aggregate of inorganic particles, respectively, The intermediate composite material The composite material constituting teeth, The inorganic particles dispersed in the resin matrix are composed of an aggregate of inorganic spherical particles having a predetermined average primary particle diameter within a range of 100 to 1000 nm, and each inorganic spherical particle constituting the aggregate is composed of substantially the same substance, and includes one or more "spherical particle groups of the same diameter" (G-PID) in which 90% or more of the total number of particles in the number-based particle size distribution of the aggregate exists within a range of 5% around the predetermined average primary particle diameter, and also includes "ultrafine particle groups" (G-SFP) consisting of inorganic particles having an average primary particle diameter of less than 100 nm, and when the number of the "spherical particle groups of the same diameter" contained in the inorganic particles is defined as a, each "spherical particle group of the same diameter" is classified into G-PIDs in order of decreasing average primary particle diameter. m (However, m is 1 when a is 1, and is a natural number from 1 to a when a is 2 or more.) When a is 2 or more, each G-PID m The materials constituting the individual particles of the G-PID may be different from each other, and in this case, m The average primary particle diameter of the "ultrafine particle group" (G-SFP) is different from that of the G-PID by 25 nm or more. 1 The average primary particle size of the resin matrix is ​​25 nm or more smaller than the average primary particle size of the resin matrix, and the refractive index of the resin matrix is ​​n (MX) Each of the G-PIDs m The refractive index of the inorganic spherical particles that make up (G-PIDm) When (G-PIDm) For n(MX) <n (G-PIDm) and is a function that represents the probability that other inorganic spherical particles are present at a point distant r from the center of any inorganic spherical particle dispersed in the composite material, and is determined based on a scanning electron microscope image in which an internal surface of the composite material is used as an observation plane, and is expressed by the formula: g(r) = {1 / 〈ρ〉} × {dn / da} When the function g(r) defined by the formula: is used as the radial distribution function, the arrangement structure of the inorganic spherical particles constituting the entire "spherical particle group of the same particle size" (G-PID) in the resin matrix is ​​expressed as the distance from the center of any inorganic spherical particle dispersed in the composite material: r, the average particle diameter of all the inorganic spherical particles dispersed in the composite material: r. 0 The dimensionless number (r / r 0 ) on the x-axis, the radial distribution function: g(r) on the y-axis, and the r / r 0 In a radial distribution function graph showing the relationship between g(r) and the r at that time, the nearest interparticle distance is defined as r corresponding to the peak top of the peak that is closest to the origin among the peaks that appear in the radial distribution function graph: r 1 is the average particle size of all inorganic spherical particles dispersed in the composite material: r 0 The condition that the value is 1 to 2 times greater than the distance between the nearest neighboring particles, and the r corresponding to the peak top of the second closest peak from the origin among the peaks appearing in the radial distribution function graph is the next nearest neighboring particle distance: r 2 When the distance between the nearest particles is: r 1 and the distance between the next nearest neighboring particles: r 2 and the minimum value of the radial distribution function: g(r) between is 0.56 or more and 1.10 or less. By doing so, Expresses a structural color of a specific tone regardless of the angle of incidence of light It is The thickness of the intermediate layer is 0.1 mm to 3 mm, and the color of the composite material is measured by a spectrophotometer against a white background for a sample having a thickness of 1.0±0.1 mm. * Value, a * value and b * The color difference between the two composite materials is expressed as a value, and the difference between the above parameters of the two composite materials is expressed as ΔL * , Δa * and Δb * Using the following formula: ΔE * = {(ΔL * ) 2 +(Δa * ) 2 +(Δb * ) 2} 1 / 2 Color difference defined as: ΔE * The color difference between the color of the first layer and the color of the second layer is expressed as ΔE * 1-2 is in the range of 2 to 30, and the color difference representing the difference between the color of the first layer and the color of the intermediate layer is: ΔE * 1-M is in the range of 2 to 25, and the color difference representing the difference between the color of the second layer and the color of the intermediate layer is: ΔE * 2-M The laminated dental resin blank for cutting is characterized in that the ratio of the surface roughness to the surface roughness is within the range of 5 to 30.

[0012] In the laminated resin-based blank for dental cutting of the above-mentioned form (hereinafter also referred to as "the blank of the present invention"), it is preferable that the multilayer structure in the cutting processing portion is a three-layer structure consisting of the first layer, the second layer and the intermediate layer.

[0013] It is also preferable that the first composite material has a color similar to the incisal color, the second composite material has a color similar to the cervical color, and the intermediate composite material is substantially free of pigments and / or dyes and exhibits a structural color with a wavelength of 550 to 770 nm.

[0014] Furthermore, the transparency of the composite material was measured by measuring the color difference of a sample having a thickness of 1.0±0.1 mm using a spectrophotometer, and the Y value was measured against a white background: W and Y value on black background:Y B Using and, the ratio of the two: Y B / Y W When the contrast ratio: CR defined by the value is expressed as an index, the contrast ratio: CR1 of the first composite material and the contrast ratio: CR2 of the second composite material are both 0.50 to 0.65 (however, CR1 and CR2 may be different values), and the contrast ratio: CR of the intermediate composite material is M It is preferable that the ratio is 0.28 to 0.46. Effect of the Invention

[0015] The blank of the present invention can express a smooth gradation from the cervical to the incisal part to a high degree. Moreover, only one intermediate layer is required as a color transition layer, and color adjustment using a pigment or dye is not required. In addition, even if different "combinations of the incisal color system and the cervical color system" are adopted for the first and second layers arranged at both ends of the intermediate layer, there is no need to change the intermediate layer. Therefore, compared with the method disclosed in Patent Document 3, in which the chromaticity difference and transparency difference between the three layers are highly adjusted and laminated, the method has superior versatility and productivity. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0016] The inventors of the present invention have conducted research on the idea that by interposing a hybrid resin layer (hereinafter also referred to as a "structural color resin layer") that exhibits a structural color as an intermediate layer between hybrid resin layers (hereinafter also referred to as "toned color resin layers") that are toned to the cervical color and the incisal color, the "effect of being able to blend in a wide variety of surrounding environments" of the structural color resin layer can be exhibited, and the structural color resin layer can blend in with the cervical color near the cervical area and with the incisal color near the incisal area, resulting in a smooth color transition from the cervical color to the incisal color. As a result, it was found that the desired effect can be obtained in some cases and not in other cases. Therefore, as a result of conducting research on the conditions under which the above-mentioned effect can be reliably obtained, it was found that the above-mentioned hardening can be reliably obtained when the thickness of the intermediate layer and the color difference (color difference) between each layer are within a specific range, and this has led to the completion of the present invention.

[0017] Although the present invention is not bound by any theory, it is believed that the reason why smooth color transition is possible by controlling the thickness of the intermediate layer is as follows. That is, when the thickness of the intermediate layer (structural color resin layer) exceeds the upper limit, the light reflecting the color of the first layer or the second layer (toning resin layer) does not reach the center, so that, as in the case of a white background, the color adjustment effect of the structural color is not obtained and the original color of the structural color resin layer is expressed, which makes it look unnatural. Conversely, when the thickness of the intermediate layer exceeds the lower limit, the light reflecting the color of the first layer and the light reflecting the color of the second layer collide directly (without attenuation) in the intermediate layer, so that it is believed that it cannot function as a color transition layer. On the other hand, when the thickness of the intermediate layer is within the range specified in the present invention, it is believed that the light reflecting the color of the first layer and the light reflecting the color of the second layer travel through the intermediate layer while being attenuated (while these colors are gradually weakened) and collide near the center. At this time, the light reflecting each color traveling through the intermediate layer is combined with the light reflecting the structural color originating from the intermediate layer, so a natural gradation can be seen within the intermediate layer. Furthermore, the color difference that represents the difference in color between the first and second layers: ΔE * 1-2 and the color difference between the color of the first layer and the color of the intermediate layer: ΔE* 1-M and the color difference between the color of the second layer and the color of the intermediate layer: ΔE * 2-M It is believed that by keeping the values ​​of each within a certain range, the layers are appropriately blurred, resulting in a smooth overall color tone transition.

[0018] The blank of the present invention will be described in detail below. In this specification, unless otherwise specified, the expression "x to y" using the numerical values ​​x and y means "greater than or equal to x and less than or equal to y". In such an expression, when a unit is added only to the numerical value y, the unit is also applied to the numerical value x. In addition, unless otherwise specified, the refractive index means the refractive index at 25°C measured with the sodium D line.

[0019] 1. Overview of the Blank of the Present Invention The blank of the present invention is a dental resin blank for cutting, having a cutting part made of a composite material (corresponding to a hybrid resin) in which inorganic particles are dispersed in a resin matrix. In order to obtain the above-mentioned effects, the blank is characterized in that it satisfies the following conditions [1] to [3].

[0020] [1] The machined portion has a multilayer structure including a three-layer structure in which an intermediate layer (structural color resin layer) made of an intermediate composite material, i.e., a hybrid resin (hereinafter also referred to as a "structural color hybrid resin") that exhibits a structural color of a predetermined color that is not dependent on the angle of incidence of light (hereinafter also referred to as a "specific structural color"), is arranged on both ends of the intermediate layer (structural color resin layer), and layers (toning resin layers) made of a first composite material and a second composite material, i.e., composite materials containing pigments and / or dyes and having different predetermined color tones (hereinafter also referred to as a "non-structural color hybrid resin" because the expression of the specific structural color is no longer visible to the naked eye).

[0021] [2] The thickness of the intermediate layer is within a specific range, specifically, 0.1 mm to 3 mm.

[0022] [3] Color difference between layers: ΔE* 1-2 , ΔE * 1-M and ΔE * 2-M The points where the value of ΔE is in a specific range. * 1-2 =2~30, ΔE * 1-M =2 to 25 and ΔE * 2-M =Be within the range of 5 to 30.

[0023] The blank of the present invention is not particularly different from a conventional hybrid resin-based dental cutting blank except that it satisfies the above three conditions, and may have a holding member for fixing it to a cutting machine, such as a holding pin, if necessary. The shape and size of the part to be cut are also not particularly limited, and may be a (solid) block formed into a rectangular parallelepiped or cylindrical shape, or a (solid) disk formed into a plate or board shape.

[0024] Each of the above conditions will be explained below.

[0025] 2. Regarding condition [1] The first composite material, the second composite material and the intermediate composite material are all hybrid resins, i.e., composite materials in which inorganic particles are dispersed in a resin matrix. However, the first composite material and the second composite material are non-structural color hybrid resins whose color is adjusted by blending pigments and / or dyes, whereas the intermediate composite material requires the use of a structural color hybrid resin that expresses a specific structural color in order to obtain a natural gradation in a single intermediate layer.

[0026] In the blanks of the present invention, the color of the first composite material and the second composite material is determined by ΔE * 1-2= 2 to 30 is not particularly limited, but it is preferable that the first composite material has a color of the incisal color system, and the second composite material has a color of the cervical color system. Here, the colors of the incisal color system and the cervical color system each have a range, and it is difficult to define them in general, but when describing qualitatively and relatively in combination in one tooth, the color of the cervical color system is the color near the gum of the tooth, and is more reddish and less blueish than the color of the incisal color system, and is also lower in brightness. In addition, the transparency is lower in the cervical part (second composite material) than in the incisal color system (first composite material).

[0027] The cut part of the blank of the present invention may have a three-layer structure of a first layer, a second layer, and an intermediate layer, or may have a four-layer structure of four or more layers with one or more layers added to the outside of the first layer and / or the second layer, so long as it has the above-mentioned multi-layer structure. The above-mentioned three-layer structure is preferable because it requires less cost and effort to manufacture and can provide a "smooth color transition" sufficient for practical use.

[0028] The intermediate composite material contains inorganic spherical particles having a predetermined average (primary) particle size and a predetermined particle size distribution, similar to the composite material used in the structural color resin blank described in Patent Document 4, and expresses a structural color (specific structural color) of a predetermined color that is not dependent on the incident angle of light (corresponding to the average particle size of the spherical particles of the same particle size contained). Here, expressing a specific structural color means that when the spectral reflectance is measured for the cured product (specifically, a cured product sample having a thickness of 1 mm) using a spectrophotometer, a peak (maximum point) derived from the specific structural color is observed in a specific wavelength range in the measurement against a black background, whereas the peak (maximum point) derived from the specific structural color is not observed in the measurement against a white background (due to the influence of reflected light from the background). Hereinafter, the peak wavelength observed in the measurement against such a black background is referred to as the wavelength of the specific structural color. From the viewpoint of effect, it is preferable that the structural color hybrid resin that becomes the intermediate composite material expresses a structural color with a specific structural color wavelength of 550 to 770 nm, particularly 600 to 750 nm.

[0029] Below, we will explain the outline of the structural color hybrid resin used as the intermediate composite material and the non-structural color hybrid resin used as the first composite material and the second composite material. Note that these hybrid resins are hardened products of the raw material hardenable composition, so their details will be described later as the raw material composition used in manufacturing the blank of the present invention.

[0030] 2-1. Overview of structural color hybrid resins For the structural color hybrid resin used as the intermediate composite material, the conditions that must be satisfied in order to express a specific structural color are known (see Patent Document 5). As the intermediate composite material in the present invention, any composite material that satisfies the following conditions I to V described in Patent Document 5 can be used without any particular restrictions.

[0031] Condition I: In the resin matrix dispersion The inorganic particles contain one or more “spherical particles of uniform size” (G-PID) and “ultrafine particles” (G-SFP). G-PID is composed of an aggregate of inorganic spherical particles having a predetermined average primary particle diameter within the range of 100 to 1000 nm, and each inorganic spherical particle constituting the aggregate is composed of substantially the same material, and 90% or more of the total number of particles in the number-based particle size distribution of the aggregate are present within a 5% range around the predetermined average primary particle diameter. The average primary particle diameter of inorganic spherical particles referred to here means an average value obtained by taking a photograph of G-PID with a scanning electron microscope, selecting 30 or more particles observed within a unit field of view of the photograph, and determining the primary particle diameter (maximum diameter) of each of them. In addition, the spherical shape may be approximately spherical, and does not necessarily have to be a perfect sphere. A photograph of G-PID is taken with a scanning electron microscope, and the maximum diameter of each particle (30 or more) within the unit field of view is measured, and the average uniformity obtained by dividing the particle diameter in the direction perpendicular to the maximum diameter by the maximum diameter is 0.6 or more, more preferably 0.8 or more. G-SFP refers to an ultrafine particle group consisting of inorganic particles with an average primary particle diameter of less than 100 nm. The average primary particle diameter of inorganic particles here refers to the average value of the primary particle diameter (maximum diameter) of each of 30 or more particles selected from a unit field of view of a photograph of G-PID taken with a scanning electron microscope.

[0032] Condition II: When the number of the "spherical particle groups of the same diameter" contained in the inorganic particles is a, each of the "spherical particle groups of the same diameter" is classified into G-PID m (However, m is 1 when a is 1, and is a natural number from 1 to a when a is 2 or more.) When a is 2 or more, each G-PID m The materials constituting the individual particles of the G-PID may be different from each other, and in this case, m The average primary particle sizes of the particles differ from each other by 25 nm or more.

[0033] Condition III: The average primary particle size of the "ultrafine particle group" (G-SFP) is smaller than the average primary particle size of the G-PID1 by 25 nm or more.

[0034] Condition IV: The refractive index of the resin matrix is ​​n (MX) Each of the G-PIDs m The refractive index of the inorganic spherical particles that make up (G-PIDm) When (G-PIDm) The following relationship also holds for n (MX) <n (G-PIDm) .

[0035] Condition V: A function expressing the probability that other inorganic spherical particles are present at a point distant r from the center of any inorganic spherical particle dispersed in the composite material, which is determined based on a scanning electron microscope image in which an internal surface of the composite material is used as an observation plane, and is expressed by the following formula (1) based on the average particle density of the inorganic spherical particles in the observation plane: <ρ>, the number of inorganic spherical particles present in the region between a circle at a distance r from any inorganic spherical particle in the observation plane and a circle at a distance r+dr: dn, and the area of ​​the region: da (where da = 2πr dr). g(r)={1 / 〈ρ〉}×{dn / da} ···(1) The composite material is characterized in that, when g(r) is a radial distribution function, the arrangement structure of the inorganic spherical particles constituting the entire "group of uniform diameter spherical particles" (G-PID) in the resin matrix has a short-range ordered structure that satisfies the following conditions 1 and 2:

[0036] [Condition 1] In a radial distribution function graph showing the relationship between r / r0 and the g(r) corresponding to r at that time, the x-axis represents a dimensionless number (r / r0) obtained by dividing the distance from the center of any inorganic spherical particle dispersed in the composite material by the average particle size r0 of all the inorganic spherical particles dispersed in the composite material, and the y-axis represents the radial distribution function g(r), the nearest inter-particle distance r1, which is defined as the r corresponding to the peak top of the peak closest to the origin among the peaks appearing in the radial distribution function graph, is a value between 1 and 2 times the average particle size r0 of all the inorganic spherical particles dispersed in the composite material.

[0037] [Condition 2] When r corresponding to the peak top of the peak that is second closest to the origin among the peaks appearing in the radial distribution function graph is defined as the next nearest interparticle distance: r2, the minimum value of the radial distribution function: g(r) between the nearest interparticle distance: r1 and the next nearest interparticle distance: r2 is a value of 0.56 or more and 1.10 or less.

[0038] 2-2. Overview of non-structural color hybrid resins On the other hand, the non-structural color hybrid resins used as the first composite material and the second composite material are hybrid resins in which the expression of a specific structural color cannot be visually confirmed due to not satisfying the conditions of Patent Document 5 or due to the incorporation of a large amount of pigments, etc., and are each mixed with a pigment and / or dye to produce a different color tone.

[0039] When one or more layers are added outside the first and / or second layer, the additional layers are also made of a non-structural color hybrid resin, and it is preferable that the layers added outside the first layer are in the incisal color system and are lighter in color than the first layer (if there are multiple additional layers, the layers are successively lighter in color toward the outside), and it is preferable that the layers added outside the second layer are in the cervical color system and are darker in color than the second layer (if there are multiple additional layers, the layers are successively darker in color toward the outside).

[0040] 3. Regarding condition [2] As described above, the thickness of the intermediate layer needs to be 0.1 mm to 3 mm so that the light reflecting the color tone of the first layer and the light reflecting the color tone of the second layer travel through the intermediate layer while being attenuated (these colors are gradually weakened) and collide near the center, causing a smooth color tone transition. Outside this range, it is difficult to obtain the effects of the present invention. From the viewpoint of the effect, the thickness of the intermediate layer is preferably 0.1 mm to 2 mm, and more preferably 0.3 mm to 1.5 mm. The thicknesses of the first layer and the second layer are not particularly limited, but are usually in the range of 1 to 13 mm, preferably 2 to 12 mm.

[0041] 4. Regarding condition [3] Condition [3] is the color difference between layers: ΔE * First, the color and color difference: ΔE * This article explains:

[0042] One of the color systems that express colors defined by hue, lightness, and saturation is L * , hue a * , saturation b * Expressed as L* a * b * There is a color space (color system). The degree of difference between two colors is expressed by the color difference ΔE, which is defined by the following formula: * The larger the value, the more different the colors of the two are. ΔE * = {(ΔL * ) 2 +(Δa * ) 2 +(Δb * ) 2} 1 / 2 In addition, the L for composite materials (hybrid resins) having a single color in this specification * Value, a * value and b * The value is the L value obtained by measuring a sample with a thickness of 1.0 ± 0.1 mm with a spectrophotometer against a white background. * , a * and b * Specifically, the L obtained by measuring the spectral reflectance of a white background (a standard white plate is placed on the cured product to block light) in a 5 mm diameter measurement area using a spectrophotometer (Tokyo Denshoku Corporation, "TC-1800MKII", halogen lamp: 12V100W, measurement wavelength range 380-780nm) and the reflected light 0°d method (JIS Z8722) is * , a * and b * is determined by.

[0043] For example, the color difference between the first composite material and the intermediate composite material, that is, the difference between the color of the first layer and the color of the intermediate layer, is: ΔE * 1-M is the L of the first composite material when the color difference is measured by a spectrophotometer using a sample of 1.0±0.1 mm in thickness for each of the first composite material and the intermediate composite material. * , a * and b * L * 1, a * 1 and b * 1, and L in the intermediate composite material * , a * and b* L * M , a * M and b * M Then, ΔL * =L * 1-L * M Δa * =a * 1-a * M Δb * =b * 1-b * M Therefore, ΔE * ={(L * 1-L * M ) 2 +(a * 1-a * M ) 2 +(b * 1-b * M ) 2} 1 / 2 In addition, the above ΔL * , Δa * and Δb * Whether the value of is positive or negative, i.e., which is the subtrahend (or minuend), does not have any effect because it is squared in the calculation process of ΔE.

[0044] The color difference between the first and second layers, ΔE, is calculated based on the characteristics of the structural color hybrid resin as an intermediate layer, and it is possible to express a more natural gradation. * 1-2 is in the range of 2 to 30, and the color difference representing the difference between the color of the first layer and the color of the intermediate layer is: ΔE * 1-M is in the range of 2 to 25, and the color difference representing the difference between the color of the second layer and the color of the intermediate layer is: ΔE * 2-MFrom the viewpoint of effectiveness, ΔE * 1-2 is in the range of 3 to 25, and ΔE * 1-M is in the range of 2 to 20, and ΔE * 2-M is more preferably within the range of 8 to 25, and ΔE * 1-2 is in the range of 6 to 20, and ΔE * 1-M is in the range of 4 to 15, and ΔE * 2-M It is particularly preferable that the ratio is within the range of 10 to 21.

[0045] 5. Contrast ratio: CR=Y B / Y W About Contrast ratio (CR) is an index of transparency of a composite material (resin-based material) in which inorganic particles are dispersed in a matrix resin. In the present invention, it is defined as the Y value (Y) obtained when a color difference measurement is performed on a sample with a thickness of 1.0±0.1 mm using a spectrophotometer against a white background. W Y value for background color black: Y B / Ratio: Y B / Y W The smaller the contrast ratio (CR), the higher the transparency, and the larger the CR, the lower the transparency.

[0046] Specifically, the contrast ratio is determined by measuring the spectral reflectance of a black background (light-shielded state) and a white background (light-shielded state with a standard white plate placed over the cured product) in a measurement area of ​​5 mmφ using the reflected light 0°d method (JIS Z8722) with a spectrophotometer (Tokyo Denshoku Corporation, "TC-1800MKII", halogen lamp: 12V 100W, measurement wavelength range 380-780nm).

[0047] The contrast ratio can be adjusted by adjusting the amount of ultrafine particles (G-SFP) made of inorganic particles with an average primary particle diameter of less than 100 nm, or coloring substances such as pigments and dyes.

[0048] In the blank of the present invention, the contrast ratio of the first composite material: CR1 and the contrast ratio of the second composite material: CR2 are both 0.50 to 0.65 (however, CR1 and CR2 may be different values), and the contrast ratio of the intermediate composite material: CR M is preferably 0.28 to 0.46. M If the value of CR1 or CR2 is outside the above range, it becomes difficult to observe the specific structural color, and it also becomes difficult to achieve harmony with the surrounding color tone. Also, if the value of CR1 or CR2 is outside the above range, when a dental prosthesis is manufactured that includes a portion in the base layer where no natural teeth exist, it tends to become difficult to achieve the effect of "being able to harmonize widely with various surrounding environments". From the viewpoint of effect, CR M is preferably 0.28 to 0.46, particularly preferably 0.28 to 0.43, and CR1 and CR2 are preferably 0.50 to 0.65, particularly preferably 0.55 to 0.63. M The difference between the contrast ratio of CR and CR1 (or CR2): M -CR1 (or CR2) = ΔCR = ΔY B / Y W is preferably 0.10 or more, and particularly preferably 0.12 to 0.27.

[0049] 6. Method for producing the blank of the present invention The blank of the present invention can be manufactured by obtaining a hybrid resin laminate having the laminated structure and processing it appropriately to form a cuttable part. The hybrid resins can be obtained by hardening a raw material composition consisting of a curable composition containing inorganic particles dispersed in a polymerizable monomer that is the raw material of the resin matrix, and further containing a polymerization initiator, and the hardened polymerizable monomer becomes the resin matrix, and only the polymerization initiator is consumed during polymerization and hardening, and the other components do not change even after hardening. The raw material compositions of each hybrid resin, the "structural color raw material composition" and the "non-structural color raw material composition", are described below.

[0050] 6-1. Structural color raw material composition The structural color hybrid resin is not particularly different from the composite material described in claim 1 of Patent Document 5, and its raw materials and preparation method are also not particularly different from the raw materials and preparation method described in Patent Document 5. In other words, the structural color hybrid resin, which is an intermediate composite material, can be produced by setting the dispersion state of the inorganic particles in the structural color raw material composition, which is a curable composition containing a polymerizable monomer, inorganic particles that satisfy specific conditions, and a polymerization initiator, to a specific dispersion state and then curing the composition.

[0051] 6-1-1. Polymerizable monomers that are the raw materials for structural color raw material compositions The polymerizable monomer in the structural color raw material composition is a monomer whose hardened form becomes the resin matrix of the structural color hybrid resin. As the polymerizable monomer, it is preferable to use a radical polymerizable monomer, particularly a polymerizable monomer consisting of a (meth)acrylic compound. The term "(meth)acrylic" means both "acrylic" and "methacrylic". Similarly, the term "(meth)acrylate" means both "acrylate" and "methacrylate".

[0052] Examples of (meth)acrylic compounds that can be suitably used include methyl (meth)acrylate, ethyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, (meth)acrylic acid, N-(meth)acryloylglycine, p-vinylbenzoic acid, 2-(meth)acryloyloxybenzoic acid, 6-(meth)acryloyloxyethylnaphthalene-1,2,6-tricarboxylic acid anhydride, 13-(meth)acryloyloxytridecane-1,1-dicarboxylic acid, 2-(meth)acrylamido-2-methylpropanesulfonic acid, 2-hydroxyethyl (meth)acrylate, 3-hydroxypropyl (meth)acrylate, N-hydroxypropyl (meth)acrylate, 1 ... Examples of the copolymer include ethyl (meth)acrylamide, N,N-(dihydroxyethyl)(meth)acrylamide, 2,2-bis(methacryloyloxyphenyl)propane, 2,2-bis[(3-methacryloyloxy-2-hydroxypropyloxy)phenyl]propane, ethylene glycol dimethacrylate, triethylene glycol dimethacrylate, 1,6-bis(methacrylethyloxycarbonylamino)trimethylhexane, trimethylolpropane trimethacrylate, pentaerythritol tetramethacrylate, neopentyl glycol dimethacrylate, and 4,4-diphenylmethane diisocyanate.

[0053] As the polymerizable monomer, in order to adjust the physical properties (mechanical properties and adhesiveness to tooth substance in dental applications) of the hardened body that becomes the resin matrix of the structural color hybrid resin, generally, multiple types of polymerizable monomers are used. In this case, it is desirable to set the type and amount of the polymerizable monomer so that the refractive index of the polymerizable monomer composition (mixture) measured using sodium D line at 25 ° C. is in the range of 1.38 to 1.55, from the viewpoint of easily satisfying the conditions related to the refractive index. The refractive index of the polymerizable monomer and the hardened body of the polymerizable monomer can be obtained using an Abbe refractometer.

[0054] 6-1-2. Inorganic particles as raw materials for structural color raw material composition The structural color raw material composition contains inorganic particles in an amount of usually 100 to 900 parts by weight, preferably 150 to 700 parts by weight, based on 100 parts by weight of the polymerizable monomer. The inorganic particles contained in the structural color raw material composition are also inorganic particles dispersed in the resin matrix of the structural color hybrid resin, and contain one or more "spherical particles of the same particle size" (G-PID). In order for the inorganic spherical particles constituting the G-PID to be dispersed in the matrix material so as to have a short-range ordered structure that satisfies the above conditions, it is preferable that the inorganic particles do not contain inorganic particles (regardless of their shape) having an average primary particle size in the range of 100 to 1000 nm other than the G-PID. However, the ultrafine particle group (G-SFP) with an average primary particle diameter of less than 100 nm is unlikely to affect the short-range ordered structure, and has the function of controlling the viscosity of the structural color raw material composition and the contrast ratio of the structural color hybrid resin depending on the amount of the ultrafine particle group (G-SFP), so it is preferable to mix it in the range of 0.1 to 40 parts by mass, especially 0.2 to 30 parts by mass, per 100 parts by mass of the polymerizable monomer.

[0055] When the structural color raw material composition is substantially free of coloring substances such as dyes and pigments (for example, when the concentration of the coloring substances is 100 mass ppm or less, preferably 50 mass ppm or less), and the amount of G-SFP is within this range, the contrast ratio of the resulting structural color hybrid resin can be set to 0.28 to 0.46.

[0056] The amount of the spherical particles of the same particle size: G-PID is usually 100 to 900 parts by mass relative to 100 parts by mass of the polymerizable monomer, which is the total amount of all G-PIDs contained (i.e., the total amount of inorganic spherical particles). Since the structural color hybrid resin has moderate transparency and has a high effect of expressing structural color, the amount of G-PID is preferably 100 to 900 parts by mass, and more preferably 150 to 700 parts by mass, relative to 100 parts by mass of the polymerizable monomer, when the structural color raw material composition does not contain ultrafine particles (G-SFP). In addition, when G-SFP is contained, it is preferable to subtract the amount of G-SFP from the above amount.

[0057] In addition, when multiple types of G-PID are included, the amount of each G-PID should be appropriately allocated so that the total amount is within the above range, taking into consideration the color tone of the structural color of each G-PID and the desired color tone of the dental cutting blank.

[0058] The inorganic spherical particles, G-PID, G-SFP, and the like constituting the inorganic particles will be described in detail below.

[0059] (1) Inorganic spherical particles As the materials of the inorganic spherical particles constituting G-PID and the inorganic particles constituting G-SFP, amorphous silica, silica-titanium group element oxide composite oxide particles (silica-zirconia, silica-titania, etc.), quartz, alumina, barium glass, strontium glass, lanthanum glass, fluoroaluminosilicate glass, ytterbium fluoride, zirconia, titania, colloidal silica, etc. can be used. Among these, silica-titanium group element oxide composite oxides, which are composite oxides of silica and titanium group element (group 4 element of the periodic table) oxide, are preferred because of their easy adjustment of refractive index, and in particular, the refractive index at 25°C can be changed in the range of about 1.45 to 1.58. Specific examples of silica-titanium group element oxide composite oxide particles include silica-titania, silica-zirconia, and silica-titania-zirconia.

[0060] The inorganic spherical particles may be surface-treated with a silane coupling agent.

[0061] (2) Group of spherical particles with the same particle size: G-PID From the viewpoint of effect, it is preferable that the structural color hybrid resin that becomes the intermediate composite material expresses a structural color with a wavelength (peak wavelength measured against a black background) of the specific structural color described above of 550 to 770 nm, and therefore, the average primary particle diameter of G-PID is preferably 230 to 800 nm, particularly preferably 240 to 500 nm, and particularly preferably 260 to 350 nm. The G-PID contained in the inorganic particles contained in the structural color raw material composition (dispersed in the resin matrix in the structural color hybrid resin such as the first composite material) may be one type or multiple types. The number of G-PIDs contained: a is preferably 1 to 5, particularly preferably 1 to 3, and most preferably 1 or 2.

[0062] When multiple G-PIDs are used, each G-PID m Average primary particle diameter d m are different from each other by more than 30 nm, especially more than 40 nm (i.e., d m and d m―1 The difference between the thickness and the thickness is preferably 30 nm or more, and more preferably 40 nm or more. m and d m―1 The difference between them is preferably 100 nm or less, and more preferably 60 nm or less.

[0063] In addition, when a structural color hybrid resin contains multiple G-PIDs, each G-PID has a very sharp particle size distribution, and the average primary particle diameter has the above-mentioned difference, so the particle size distributions of each G-PID are unlikely to overlap, and even if they overlap, it is possible to confirm the particle size distribution of each G-PID. That is, the particle size distribution of inorganic particles has the same number of independent peaks as the number of G-PIDs contained in the range of 100 nm to 1000 nm, and even if each peak overlaps partially, the average primary particle diameter and number-based particle size distribution of each G-PID can be confirmed by performing waveform processing. In addition, the particle size distribution of inorganic particles contained in a structural color hybrid resin such as the first composite material can be confirmed, for example, by image processing an electron microscope photograph of its internal surface.

[0064] At least a part of the one or more "same-sized spherical particle groups" (G-PID) comprises one type of "same-sized spherical particle groups" (G-PID) and a resin whose refractive index at 25°C is smaller than that of the inorganic spherical particles constituting the one type of "same-sized spherical particle groups" (G-PID), and is preferably blended as an organic-inorganic hybrid filler that does not contain any "same-sized spherical particle groups" (G-PID) other than the one type of "same-sized spherical particle groups" (G-PID), in other words, an "organic-inorganic hybrid filler that contains only a single G-PID." Here, the organic-inorganic hybrid filler is a composite consisting of an inorganic filler dispersed in an (organic) resin matrix. powder or an aggregate in which primary particles of inorganic filler are bound together by (organic) resin. powder means.

[0065] The average particle size of the organic-inorganic composite filler is not particularly limited, but from the viewpoint of improving the mechanical strength of the cured body and the handleability of the curable paste, it is preferably 2 to 100 μm, more preferably 5 to 50 μm, and particularly preferably 5 to 30 μm.

[0066] The amount of the organic-inorganic composite filler in the raw material composition may be determined by converting the amount of the inorganic spherical particles contained in the organic-inorganic composite filler into the amount of G-PID, a group of spherical particles having the same particle size that is not formed into an organic-inorganic composite filler and is contained in the raw material composition, so that the total amount of all G-PID contained (i.e., the total amount of inorganic spherical particles) is the amount described above.

[0067] (3) Ultrafine particle group: G-SFP The average primary particle size of G-SFP is preferably 3 nm to 75 nm, particularly 5 nm to 50 nm, because it has little effect on the expression of structural color. For the same reason, it is preferably 30 nm or more, particularly 40 nm or more smaller than the average primary particle size (d1) of G-PID1.

[0068] The material of the inorganic particles constituting G-SFP can be the same as that of the inorganic spherical particles without any particular limitation. Also, surface treatment can be performed with a silane coupling agent in the same manner as that of the inorganic spherical particles. The preferred embodiment is also basically the same as that of the inorganic spherical particles, except for the average primary particle size and shape.

[0069] 6-1-3. Polymerization initiators as raw materials for structural color raw material compositions The polymerization initiator, which is the raw material of the structural color raw material composition, is not particularly limited as long as it has the function of polymerizing and curing the polymerizable monomer, but photopolymerization and thermal polymerization are preferred, and thermal polymerization is particularly preferred because it is less likely to cause polymerization unevenness due to light irradiation and can perform a uniform polymerization reaction. Examples of the thermal polymerization initiator include peroxides such as benzoyl peroxide, p-chlorobenzoyl peroxide, tert-butylperoxy-2-ethylhexanoate, tert-butylperoxydicarbonate, and diisopropylperoxydicarbonate, azo compounds such as azobisisobutyronitrile, boron compounds such as tributylborane, tributylborane partial oxide, sodium tetraphenylborate, sodium tetrakis(p-fluorophenyl)borate, and triethanolamine salt of tetraphenylborate, barbituric acids such as 5-butylbarbituric acid and 1-benzyl-5-phenylbarbituric acid, and sulfinic acid salts such as sodium benzenesulfinate and sodium p-toluenesulfinate.

[0070] These polymerization initiators may be used alone or in combination of two or more. It is also possible to combine a plurality of initiators which use different polymerization methods.

[0071] The amount of the polymerization initiator to be added may be selected according to the purpose, and is usually 0.01 to 10 parts by mass, more preferably 0.1 to 5 parts by mass, per 100 parts by mass of the polymerizable monomer.

[0072] The polymerization temperature when using a thermal polymerization initiator is preferably 60 to 200°C, more preferably 70 to 150°C, and even more preferably 80 to 130°C. If polymerization is performed at a temperature below 60°C, the polymerization reaction becomes insufficient, the strength of the dental cutting blank is weakened, and cracks occur. On the other hand, if polymerization is performed at a temperature above 200°C, the structural color hybrid resin is exposed to high temperatures during production, causing discoloration of the resin component, making it difficult to achieve the effect of the present invention of matching color with natural teeth.

[0073] 6-1-4. Other additives that are used as raw materials for structural color raw material compositions The structural color raw material composition may contain other additives such as polymerization inhibitors and ultraviolet absorbers, as long as they do not impair the effect of the structural color raw material composition. It is preferable that the structural color hybrid resin that is the intermediate composite material does not substantially contain coloring substances such as dyes and pigments. Here, "substantially does not contain" means that the amount of coloring substances based on the total mass of the structural color raw material composition (which is also the total mass of the first composite material) is 50 mass ppm or less.

[0074] 6-1-5. Method for preparing structural color raw material composition The raw material composition can be prepared by kneading and defoaming predetermined amounts of each of the above-mentioned components. In particular, it is preferable to use a kneading device such as a planetary stirrer for the kneading method, because it is possible to disperse the components in a short time and it is easy to scale up the production. In addition, it is preferable to use a method of defoaming under reduced pressure, because it is possible to remove bubbles in a short time even from a highly viscous composition.

[0075] 6-2. Non-structural color raw material composition The non-structural color hybrid resin that becomes the first composite material or the second composite material is a hybrid resin that is not a structural color hybrid resin, or a hybrid resin in which a specific structural color cannot be visually confirmed due to the incorporation of a large amount of pigment, etc., and is obtained by curing a "non-structural color raw material composition," which is a polymerizable and curable composition containing a coloring material consisting of a polymerizable monomer, inorganic particles, a polymerization initiator, and a pigment and / or a dye.

[0076] The non-structural color raw material composition may be a structural color raw material composition to which a coloring material (in an amount such that the specific structural color cannot be visually confirmed) has been added, and the same polymerizable monomer and polymerization initiator as those in the structural color raw material composition can be used. The inorganic particles are not particularly restricted as in the structural color raw material composition, and those that are considered to be usable in conventional dental cutting resin blanks can be used without any particular restrictions. The total amount of inorganic particles is usually 100 to 900 parts by weight, preferably 150 to 700 parts by weight, per 100 parts by weight of the polymerizable monomer. The amount of the coloring substance contained in the non-structural color raw material composition is usually 500 to 7000 ppm by weight, preferably 600 to 6500 ppm by weight, based on the total mass of the non-structural color raw material composition (which is also the total mass of the composite material that is its cured body). In addition, other additives such as polymerization inhibitors and ultraviolet absorbers may be included.

[0077] The coloring material (colorant) may be a pigment or a dye. The pigment is typically an inorganic pigment, and examples of such inorganic pigments include titanium oxide, zinc oxide, zirconium oxide, zinc sulfide, aluminum silicate, calcium silicate, carbon black, iron oxide, copper chromite black, chromium oxide green, chrome green, violet, chrome yellow, lead chromate, lead molybdate, cadmium titanate, nickel titanium yellow, ultramarine blue, cobalt blue, bismuth vanadate, cadmium yellow, and cadmium red. In the present invention, the inorganic pigment also corresponds to an inorganic filler. In addition, organic pigments such as monoazo pigments, diazo pigments, diazo condensation pigments, perylene pigments, and anthraquinone pigments can also be used. Examples of dyes include red dyes such as KAYASET RED G (Nippon Kayaku) and KAYASET REDB (Nippon Kayaku), yellow dyes such as KAYASET Yellow 2G and KAYASET Yellow GN, and blue dyes such as KAYASET Blue N, KAYASET Blue G and KAYASET Blue B. Considering color stability in the oral cavity, it is preferable to use water-insoluble pigments rather than water-soluble dyes. By adding this, it becomes possible to meet such demands.

[0078] 6-3. Casting polymerization and post-processing The hybrid resin laminate can be suitably manufactured by casting polymerization using a curable raw material composition that is a raw material for the hybrid resin (composite) that constitutes each layer. Here, casting polymerization means that a polymerizable curable composition is filled into a mold of a predetermined shape, and then polymerization and curing are performed. The volume of the mold may be appropriately selected according to the desired shape. Similarly, the shape of the mold may be a rectangular column, a cylindrical column, a square plate, a disk, or other irregular shape, and is not particularly limited. During polymerization, pressure may be applied with an inert gas such as nitrogen, as necessary. A mold having the same or substantially the same shape as the part to be cut is prepared, and the curable raw material composition that will be each layer is filled in sequence to a predetermined thickness inside the mold, and then polymerized and cured, and the obtained bulk body (hybrid resin laminate) may be used as the part to be cut as it is, or a bulk body may be manufactured by filling a mold having a larger size, and the bulk body may be punched or cut to be the part to be cut. The filling method can be a known technique and is not particularly limited, but for example, the mold can be filled by injection, extrusion, pressing, etc.

[0079] The material of the mold may be metal, ceramic, resin, etc., depending on the purpose, and it is preferable to use a material that has a higher heat resistance than the polymerization temperature to be carried out. Examples of the material of the mold include SUS, high-speed tool steel, aluminum alloy, polyethylene terephthalate (PET), polyethylene (PE), polypropylene (PP), polystyrene (PS), etc.

[0080] In addition, the obtained bulk body can be subjected to post-processing such as heat treatment, polishing, cutting, attachment of a holder, printing, etc., as necessary. Furthermore, a holding pin for fixing the dental cutting blank to a cutting machine can be joined as necessary. The shape of the holding pin is not particularly limited as long as it can fix the dental cutting blank to the cutting machine, and may not be provided depending on the shape of the dental cutting blank and the requirements of the processing machine. Examples of materials for the holding pin include stainless steel, brass, aluminum, etc. The method of fixing the holding pin to the part to be cut (dental cutting blank body) is not limited to adhesion, and may be a method such as fitting or screwing. There is also no particular limitation on the adhesion method, and various commercially available adhesives such as isocyanate-based, epoxy-based, urethane-based, silicone-based, and acrylic-based adhesives can be used. EXAMPLES

[0081] Next, the multilayer mill blank of the present invention will be specifically described by examples. In each of the examples and comparative examples described below, various structural color raw material compositions and non-structural color raw material compositions are prepared, and the obtained compositions and their cured bodies are evaluated. In addition, these compositions are laminated in a predetermined combination and then cured to obtain a hybrid resin laminate that will be the cutting part of the dental cutting blank, and the evaluation is performed.

[0082] 1. Raw materials for structural color raw material composition and non-structural color raw material composition The raw materials of the structural color raw material compositions and non-structural color raw material compositions used in the examples and comparative examples, as well as their physical properties, will be described below.

[0083] 1-1. Polymerizable monomer components As the polymerizable monomer component in the structural color raw material composition and the non-structural color raw material composition, a polymerizable monomer mixture M1 having a composition of 60 mass% 1,6-bis(methacrylethyloxycarbonylamino)trimethylhexane (sometimes abbreviated as UDMA) and 40 mass% triethylene glycol dimethacrylate (sometimes abbreviated as 3G) was used.

[0084] The viscosity of M1 was measured in a thermostatic chamber at 25°C using an E-type viscometer (Tokyo Seiki: VISCONIC ELD) and found to be 150.14 (mPa·s). The refractive index of M1 (before curing) and its cured body was measured in a thermostatic chamber at 25°C using an Abbe refractometer (Atago Co., Ltd.). The refractive index before curing was 1.474 and the refractive index after curing was 1.509. The cured body sample was prepared by adding (as a photopolymerization initiator) 0.2% by mass of camphorquinone (CQ), 0.3% by mass of ethyl pN,N-dimethylaminobenzoate (DMBE) and 0.15% by mass of hydroquinone monomethyl ether (HQME) per 100 parts by mass of polymerizable monomer, and mixing the mixture uniformly. The mixture was placed in a mold with a through hole of 7 mmφ×0.5 mm, and polyester films were pressed onto both sides. The mixture was then exposed to a light intensity of 500 mW / cm. 2 The specimen was then cured by irradiating it with light for 30 seconds using a halogen-type dental light irradiator (Demetron LC, manufactured by Cybron) and then removed from the mold. When the cured specimen was set in the Abbe refractometer, bromonaphthalene, a solvent that does not dissolve the specimen and has a higher refractive index than the specimen, was dropped onto the specimen in order to bring the cured specimen into close contact with the measurement surface.

[0085] 1-2. Group of spherical particles with the same particle size: G-PID According to the method disclosed in the examples of Patent Document 5, a spherical filler made of a composite oxide with a SiO2 / ZrO2 / Na2O molar ratio composition of 89.8 / 9.0 / 1.2 was prepared by a sol-gel method, and surface-treated with γ-methacryloyloxypropyltrimethoxysilane to prepare G-PID1 and G-PID2, which are spherical particle groups of the same particle size. The average primary particle size, the ±5% particle ratio [the ratio (%) of the number of particles present within a 5% range around the average primary particle size in the number-based particle size distribution to the total number of particles], the average uniformity, and the refractive index of the obtained G-PID1 were measured as follows, in the same manner as described in the examples of Patent Document 5. The results are shown in Table 1.

[0086] (1) Average primary particle diameter Photographs of the powder were taken at magnifications of 5,000 to 100,000 times using a scanning electron microscope (Philips, "XL-30S"), and the images were processed using image analysis software ("IP-1000PC", product name; Asahi Kasei Engineering Corporation). The number of particles observed within a unit field of view of the photograph (30 or more) and the primary particle diameter (maximum diameter) were measured, and the number average primary particle diameter was calculated based on the measured values ​​(the sum of the measurements divided by the number of particles).

[0087] (2) Particle ratio within ±5% Of all particles (30 or more) in the unit field of view of the photograph, the number of particles having a primary particle diameter (maximum diameter) outside the particle diameter range of 5% around the average primary particle diameter obtained above was counted, and this value was subtracted from the total number of particles to obtain the number of particles within the particle diameter range of 5% around the average primary particle diameter in the unit field of view of the photograph, and calculated according to the following formula.

[0088] Percentage of particles within ±5% (%) = [(Number of particles within a particle size range of 5% around the average primary particle size in a unit field of view of a scanning electron microscope photograph) / (Total number of particles in a unit field of view of a scanning electron microscope photograph)] × 100

[0089] (3) Average symmetry A photograph of the powder was taken with a scanning electron microscope, and the number (n: 30 or more) of spherical particles of the same diameter (G-PID) observed within a unit field of view of the photograph was determined, and the ratio (Bi / Li) of the maximum diameter of the particle (long diameter (Li)) to the diameter in the direction perpendicular to the long diameter (Bi) was calculated. The sum of these ratios was divided by the number of particles to obtain the average uniformity.

[0090] (4) Refractive index The measurement was performed by the immersion method using an Abbe refractometer (manufactured by Atago Co., Ltd.). That is, in a thermostatic room at 25°C, a group of spherical particles of the same particle size (G-PID) was dispersed in 50 ml of anhydrous toluene in a 100 ml sample bottle. While stirring this dispersion with a stirrer, 1-bromotoluene was added dropwise little by little, and the refractive index of the dispersion at the point when the dispersion became most transparent was measured, and the obtained value was taken as the refractive index of the group of spherical particles of the same particle size (G-PID).

[0091] [Table 1]

[0092] 1-3. Organic-inorganic composite filler (CF) The organic-inorganic composite filler (CF) was also prepared as follows using G-PID2 shown in Table 1, in the same manner as in the examples of Patent Document 5. That is, first, a dispersion in which 100 g of G-PID2 was dispersed in 200 g of water was obtained using a circulation type grinder SC Mill (manufactured by Nippon Coke Engineering Co., Ltd.). Next, a mixed solution (pH 4) of 4 g of γ-methacryloyloxypropyltrimethoxysilane, 0.003 g of acetic acid, and 80 g of water, which had been separately prepared, was added to the dispersion and mixed until uniform. After that, the dispersion was lightly mixed and supplied onto a disk rotating at high speed to be granulated by a spray drying method, and then vacuum dried at 60° C. to obtain an aggregate having a roughly spherical shape. Then, 50 g of the above aggregates were immersed in a polymerizable monomer solution containing 10 g of polymerizable monomer component M1, 0.025 g of azobisisobutyronitrile (AIBN) as a thermal polymerization initiator, and 5.0 g of methanol as an organic solvent. After thorough stirring, the organic solvent was removed, and the mixture was heated for 1 hour under conditions of a reduced pressure of 10 hectopascals and 100°C to polymerize and harden the above polymerizable monomer component, thereby obtaining an organic-inorganic composite filler (CF) with a roughly spherical shape and an average particle size of 12 μm.

[0093] 1-4. Ultrafine particles (G-SFP) As the G-SFP, Rheolosil QS-102 (average primary particle diameter 12 nm, manufactured by Tokuyama Corporation) was used.

[0094] 1-5. Polymerization initiator A thermal polymerization initiator consisting of benzoyl peroxide (BPO) was used.

[0095] 1-6.Pigments · Red pigment (Pigment Red 166) Yellow pigment (Pigment Yellow 95) ·Blue pigment (Pigment Blue 60).

[0096] 2. Preparation of structural color raw material composition and non-structural color raw material composition and evaluation of the hardened bodies 2-1. Preparation of structural color raw material compositions (P1 to P4) The structural color raw material composition: P1 was prepared as shown below. That is, after mixing 100 parts by mass of M1 and 1.0 parts by mass of BPO, G-PID1 and G-SFP were added so that the mass ratio of the two was G-PID1:G-SFP=95:5, and the inorganic filling rate, defined as the ratio of the mass of the total inorganic particles to the mass of the total structural color raw material composition, was 72% by mass, and the mixture was mixed until uniform using a planetary mixer to form a paste, thereby preparing the structural color raw material composition: P1.

[0097] In addition, structural color raw material compositions P2 to P4 were prepared in the same manner as above, except that the inorganic filling rate was set to the inorganic filling rate shown in Table 2.

[0098] The refractive index of the hardened body of M1 is: n (MX) is 1.509, and the refractive index of G-PID1 is n(G-PID1) = 1.515, respectively. (MX) Since the value is larger than the above, it satisfies the above condition IV. Therefore, it can be said that the hybrid resins made of the cured bodies of these structural color raw material compositions: P1 to P4 all satisfy the above conditions I to IV {P1 to P4 contain one type of G-PID, and also satisfy the above condition II.}

[0099] [Table 2]

[0100] 2-2. Preparation of non-structural color raw material compositions (L1 to L8) After mixing 100 parts by mass of M1 and 1.0 part by mass of BPO, a mixture of 50% by mass of G-PID2 and 50% by mass of CF (organic-inorganic composite filler) was added so that the inorganic filling rate was 76%. In addition, various pigments were added in the amounts shown in Table 3. Except for this, non-structural color raw material compositions: L1 to L8 were prepared in the same manner as in the preparation of P1.

[0101] [Table 3]

[0102] 2-3. Evaluation of hardened bodies of each raw material composition 2-3-1. Confirmation that the hardened bodies of the structural color raw material compositions (P1-P4) are structural color hybrid resins According to the method described in Patent Document 5, the cured products of each structural color raw material composition (P1 to P4) were visually evaluated for coloring light, measured for peak wavelength of coloring light, and evaluated for radial distribution function of inorganic spherical particles by the following methods (1) to (3). The results are shown in Table 4.

[0103] (1) Visual evaluation method for colored light The structural color raw material compositions (P1 to P4) were vacuum degassed, filled into a 10 mm x 12 mm x 14 mm mold, and the top surface was smoothed. After that, using a heating and pressure polymerization apparatus, heating and pressure polymerization was performed under nitrogen pressure at a pressure of 0.4 MPa, 100°C, and 12 hours. Solid samples of 1 mm x 12 mm x 14 mm were cut out from the removed hardened body and polished to a glossy finish to prepare solid samples for colored light measurement. Each solid sample for colored light measurement was placed perpendicular to the adhesive surface of a 10 mm square black tape (carbon tape), and the color tone of the colored light was evaluated visually.

[0104] (2) Measurement method for peak wavelength of colored light For the solid sample for colored light measurement with black tape attached, prepared in the same manner as in (1), the spectral reflectance was measured against a black background using a spectrophotometer (Tokyo Denshoku Corporation, "TC-1800MKII", halogen lamp: 12V100W, measurement wavelength range 380-780nm), and the maximum point of reflectance was taken as the wavelength of the colored light.

[0105] (3) Radial distribution function evaluation method for inorganic spherical particles A hardened body was prepared in the same manner as in (1) except that the structural color raw material compositions (P1 to P4) were filled into a mold of 5 mmφ×10 mm, and the dispersion state of the spherical particles in the hardened body was observed with a scanning electron microscope (Philips, "XL-30S") to obtain the radial distribution function and perform evaluation. Specifically, the cross-section of the hardened body was milled using an ion milling device (Hitachi, Ltd., "IM4000") at 2 kV for 20 minutes to obtain an observation plane. A microscopic image of an area containing 1000 spherical particles in the plane of the observation plane was obtained using a scanning electron microscope, and the obtained scanning electron microscope image was analyzed using image analysis software ("Simple Digitizer ver3.2" free software) to obtain the coordinates of the spherical particles in the above area. From the obtained coordinate data, the coordinates of any one spherical particle are selected, and a circle is drawn with a radius of distance r that contains at least 200 spherical particles centered on the selected spherical particle, and the number of spherical particles contained within the circle is calculated to obtain the average particle density <ρ> (unit: particles / cm 2 ) was calculated. dr is a value of about r0 / 100 to r0 / 10 (r0 indicates the average particle diameter of the spherical particles). The number of particles dn contained in the region between the circle at the distance r from the central spherical particle and the circle at the distance r + dr, and the area da of the above region (where da = 2πr dr) were calculated. Using the values ​​of <ρ>, dn, and da calculated in this way, Formula: g(r) = {1 / <ρ>} × {dn / da} The radial distribution function g(r) defined as follows was obtained. A graph showing the relationship between the radial distribution function and r / r0 (r indicates an arbitrary distance from the center of the circle, and r0 indicates the average particle diameter of the spherical particles) was then created, and the radial distribution function in Condition V was evaluated as satisfying Condition 1 and Condition 2, with "S" indicating that the condition was satisfied, and "N" indicating that the condition was not satisfied.

[0106] As shown in Table 4, it was confirmed that the dispersion state of the spherical inorganic particles in the cured products of the structural color raw material compositions (P1 to P4) satisfied the above-mentioned condition V, and that the specific structural color was expressed.

[0107] [Table 4]

[0108] 2-3-2. The brightness of each raw material composition hardened body is L * , hue a * and saturation b * and contrast ratio (CR) evaluation The cured products of the structural color raw material compositions (P1 to P4) and the non-structural color raw material compositions (L1 to L8) were subjected to L * , a * and b * The results are shown in Table 5.

[0109] (4) Lightness to L * , hue a * and saturation b * Measurement Each raw material composition was vacuum degassed, filled and packed into a 10 mm x 12 mm x 14 mm mold, and the top surface was smoothed. After that, using a heating and pressure polymerization apparatus, heating and pressure polymerization was performed under nitrogen pressure at a pressure of 0.4 MPa, 100°C, and 12 hours. A solid sample of 14 mm x 12 mm x 1 mm was cut out from the removed cured body to prepare a solid sample for color difference measurement. For this solid sample, the spectral reflectance of a background color white (a standard white plate was placed over the cured body to block light) in a measurement area of ​​5 mmφ was measured by the reflected light 0°d method (JIS Z8722) using a spectrophotometer (Tokyo Denshoku Co., Ltd., "TC-1800MKII", halogen lamp: 12V100W, measurement wavelength range 380 to 780 nm) to measure the L * Value, a * value and b * The value was calculated.

[0110] (5) Contrast ratio (CR) measurement Using the above color difference meter, the Y value of the spectral reflectance of the above sample against a black background (light-shielded state) was measured. B and Y value of the spectral reflectance of the white background (a standard white plate is placed over the cured product to block light). W Based on the contrast ratio CR=Y B / Y W was calculated.

[0111] [Table 5]

[0112] 3. Examples and Comparative Examples The above P1 to P4 and L1 to L8 pastes were used in the combinations shown in Tables 6 and 7, and a hybrid resin layer made of the hardened product of the raw material composition for the intermediate layer was bonded between a hybrid resin layer made of the hardened product of the raw material composition for the first layer and a hybrid resin layer made of the hardened product of the raw material composition for the second layer, each having the same layer thickness, with the layer thickness shown in Tables 6 and 7.A machined part made of a three-layer hybrid resin laminate was produced as follows.

[0113] That is, the raw material composition for the first layer is filled to half the height of the mold minus the thickness of the raw material composition for the intermediate layer in the mold (4.5 mm when the raw material composition for the intermediate layer is filled to 1 mm) and left to stand until the surface becomes flat, and then the raw material composition for the intermediate layer is filled to the layer thickness shown in Table 7 while being careful not to disturb the interface, and then left to stand again until the surface becomes flat, and then the raw material composition for the second layer is filled to fill the inside of the mold. * , a * and b * Hardening was carried out in the same manner as in the preparation of the measurement sample, and the above-mentioned machined portion was prepared.

[0114] The lamination interface of the obtained machined part was evaluated, and a retaining pin was attached to the machined part to make a resin blank for dental machining. The state of the lamination interface of the dental restoration (crown) made using this was evaluated, as well as the state of color change of the lamination interface. The specific evaluation method is shown below. The evaluation results were also evaluated in terms of the thickness of the intermediate layer, the color difference between the first and second layers: ΔE * , Color difference between the first layer, second layer and middle layer: ΔE * These are shown together in Tables 6 and 7.

[0115] (1) Evaluation of laminated interface (blank interface evaluation) The laminate was visually observed to confirm whether the laminate interface was visible. The evaluation criteria are as follows: 5: The interface between the middle layer and the upper or lower layer is completely invisible. 4: The interface between the middle layer and the upper or lower layer is not visible. 3: The interface between the middle layer and the upper or lower layer is barely visible. 2: The interface between the middle layer and the upper or lower layer is barely visible. 1: The interface between the middle layer and the upper or lower layer is clearly visible.

[0116] (2) Evaluation of the laminate interface of a dental imitation restoration (restoration interface evaluation) The crown of the upper right first tooth was machined using a milling machine (Roland, "DWX-50") to create a dental restoration (restoration), which was then bonded to a resin abutment (equivalent to A3 color) using Esthecem II (Tokuyama Dental, adhesive resin cement), polished, and a mock restoration was performed. The condition of the laminate interface after restoration was visually confirmed. The evaluation criteria are as follows: 5: The interface between the middle layer and the upper or lower layer is completely invisible, and the color tone is natural. 4: The interface between the middle layer and the upper or lower layer is barely visible, and the color is natural. 3: The interface between the middle layer and the upper or lower layer is difficult to see. 2: The interface between the middle layer and the upper or lower layer is faintly visible. 1: The interface between the middle layer and the upper or lower layer is clearly visible and has an unnatural color tone.

[0117] (3) Evaluation of the continuous color transfer of dental restorations (restoration transfer evaluation) The simulated restorations prepared in the same manner as in (2) were visually inspected for a continuous color change from the cervical area to the incisal area. The evaluation criteria are as follows: 5: The color tone of the upper layer changes gradually to the color tone of the lower layer, in a very natural and smooth transition. 4: The color tone of the upper layer gradually changes to the color tone of the lower layer, with a very smooth transition. 3: The color tone of the upper layer gradually changes to the color tone of the lower layer, with a smooth transition. 2: The color tone changes from the upper layer to the lower layer, which looks unnatural. 1: There is no continuous change in color tone from the upper layer to the lower layer.

[0118] [Table 6]

[0119] [Table 7]

[0120] As shown in Table 6, the "restoration transfer evaluation" of Examples 1 to 26 was 3 or more. * are both in a particularly suitable range (thickness of intermediate layer: 0.3 to 1.5 mm, ΔE * 1-2 = 6 to 20, ΔE * 1-M =4~15, ΔE * 2-M The "restoration migration evaluation" for Examples 3, 10, 13, 16, 17, and 19 (=10 to 21) was the highest evaluation of 5, and the "blank interface evaluation" for Example 17 was one rank lower, 4, but the other "blank interface evaluations" and "restoration interface evaluations" were all 5.

[0121] In contrast, the "restoration migration evaluation" of Comparative Examples 1 to 6 was 1 to 2. In Comparative Example 1, the intermediate layer was thick, so the color adjustment effect by the structural color was not obtained, as in the case of a white background, and the color of the structural color resin layer was expressed in the center, and a continuous color change was not obtained. In Comparative Example 2, in which the color difference between the first layer and the second layer was large, and Comparative Example 3, in which the color difference between the intermediate layer and the second layer was large, the layer interface was visually confirmed due to the large color difference, and the restoration migration evaluation was 2 and 1, respectively. In Comparative Example 4, in which the first layer and the second layer have the same color tone, no continuous color change was confirmed in the intermediate layer, and it was recognized as a single color overall. In Comparative Example 5, in which the structural color resin was used in the first layer as well, the color tone of the structural color resin layer was expressed, and a continuous color change was not obtained. In Comparative Example 6, which did not have an intermediate layer, a clear interface was confirmed between the dark color tone of the cervical part and the light color tone of the incisal part.

Claims

1. A dental resin blank for machining having a machining part made of a composite material in which inorganic particles are dispersed in a resin matrix, The machined portion has a multi-layer structure including a first layer, a second layer, and an intermediate layer interposed between these layers, When the composite materials constituting the first layer, the second layer and the intermediate layer are respectively a first composite material, a second composite material and an intermediate composite material, the first composite material and the second composite material contain a pigment and / or a dye and have different predetermined color tones; When the average value and number-based particle size distribution of 30 or more primary particles observed within a single visual field of a photograph of an aggregate of inorganic particles taken with a scanning electron microscope are defined as the average primary particle size and number-based particle size distribution of the aggregate of inorganic particles, respectively, The composite material constituting the intermediate composite material is the inorganic particles dispersed in the resin matrix are composed of an aggregate of inorganic spherical particles having a predetermined average primary particle diameter within a range of 100 to 1000 nm, and the individual inorganic spherical particles constituting the aggregate are composed of substantially the same material, and include one or more "spherical particle groups of the same particle diameter" (G-PID) in which 90% or more of the total number of particles in the number-based particle size distribution of the aggregate are present within a range of 5% around the predetermined average primary particle diameter, and also include "ultrafine particle groups" (G-SFP) composed of inorganic particles having an average primary particle diameter of less than 100 nm; When the number of the "spherical particle groups of the same diameter" contained in the inorganic particles is a, and each "spherical particle group of the same diameter" is expressed as G-PID m (where m is 1 when a is 1, and is a natural number from 1 to a when a is 2 or more) in order of decreasing average primary particle diameter, when a is 2 or more, the materials constituting the individual particles of each G-PID m may be different from each other, and in that case, the average primary particle diameters of each G-PID m differ from each other by 25 nm or more, The average primary particle size of the "ultrafine particle group" (G-SFP) is smaller than the average primary particle size of the G-PID 1 by 25 nm or more; When the refractive index of the resin matrix is ​​n (MX) and the refractive index of the inorganic spherical particles constituting each G-PID m is n (G-PIDm), the relationship n (MX) < n (G-PIDm) is established for any n (G-PIDm), and The function represents the probability that other inorganic spherical particles are present at a point distant r from the center of any inorganic spherical particle dispersed in the composite material, and is determined based on a scanning electron microscope image in which an internal surface of the composite material is used as an observation plane, and is based on the average particle density of the inorganic spherical particles in the observation plane: <ρ>, the number of inorganic spherical particles present in the region between a circle at a distance r from any inorganic spherical particle in the observation plane and a circle at a distance r+dr: dn, and the area of ​​the region: da (where da = 2πr dr), and is expressed by the formula: g(r)={1 / 〈ρ〉}×{dn / da} When g(r) is the radial distribution function, The arrangement structure of the inorganic spherical particles constituting the entire "spherical particle group of uniform diameter" (G-PID) in the resin matrix is a radial distribution function graph showing the relationship between r / r0 and the g(r) corresponding to r at that time, the x-axis representing a dimensionless number (r / r0) obtained by dividing the distance r from the center of any inorganic spherical particle dispersed in the composite material by the average particle size r0 of all the inorganic spherical particles dispersed in the composite material, and the y-axis representing the radial distribution function g(r), the nearest inter-particle distance r1, which is defined as the r corresponding to the peak top of the peak closest to the origin among the peaks appearing in the radial distribution function graph, is a value that is 1 to 2 times the average particle size r0 of all the inorganic spherical particles dispersed in the composite material; the short-range ordered structure satisfies the condition that, when the next nearest interparticle distance: r2 is defined as the r corresponding to the peak top of the peak that is second nearest from the origin among the peaks appearing in the radial distribution function graph, the minimum value of the radial distribution function: g(r) between the nearest interparticle distance: r1 and the next nearest interparticle distance: r2 is a value of 0.56 or more and 1.10 or less; This allows the material to exhibit a structural color of a predetermined tone regardless of the angle of incidence of light. The thickness of the intermediate layer is 0.1 mm to 3 mm, The color of the composite material was measured on a sample having a thickness of 1.0±0.1 mm using a spectrophotometer against a white background. * Value, a * Value and b * The color difference between the two composite materials is expressed as a difference between the above parameters, ΔL * , Δa * and Δb * Using the following formula: ΔE * ={(ΔL * ) 2 +(Δa * ) 2 +(Δb * ) 2 } 1/2 Color difference defined as: ΔE * When expressed as A color difference representing the difference between the color of the first layer and the color of the second layer: ΔE * 1-2 is in the range of 2 to 30, A color difference representing the difference between the color of the first layer and the color of the intermediate layer: ΔE * 1-M is in the range of 2 to 25, A color difference representing the difference between the color of the second layer and the color of the intermediate layer: ΔE * 2-M is in the range of 5 to 30; A laminated resin-based blank for dental cutting, characterized in that

2. 2. The laminated dental resin blank for cutting according to claim 1, wherein the multi-layer structure in the cutting portion is a three-layer structure consisting of the first layer, the second layer and the intermediate layer.

3. The transparency of the composite material is measured by a spectrophotometer using a sample having a thickness of 1.0±0.1 mm, and the Y value is measured against a white background. W and Y value on black background: Y B Using the above, the ratio of the two values ​​is: Y B / Y W When the contrast ratio (CR) defined by the value is expressed as an index, The contrast ratio of the first composite material is CR 1 and the contrast ratio of the second composite material: CR 2 Both are between 0.50 and 0.65 (however, CR 1 and C.R. 2 and may be different values ​​from each other. ), the contrast ratio of the intermediate composite material: CR M The laminated dental resin blank for cutting according to claim 1 or 2, wherein the σ is 0.28 to 0.

46.

4. The laminated resin-based blank for dental cutting described in any one of claims 1 to 3, wherein the first composite material has a color of the incisal color system, the second composite material has a color of the cervical color system, and the intermediate composite material is substantially free of pigments and / or dyes and exhibits a structural color with a wavelength of 550 to 770 nm.

5. the total amount of pigments and / or dyes in the first composite material is 100 ppm by mass or less relative to the total mass of the first composite material, and the total amount of pigments and / or dyes in the second composite material is 500 to 7000 ppm by mass relative to the total mass of the second composite material; A laminated resin blank for dental cutting according to any one of claims 1 to 4.

Citation Information

Patent Citations

  • dental mill blank

    JP2016535610A

  • Resin block for dental CAD / cam

    JP2017213394A

  • Composite material

    JP2020037534A

  • Composite materials

    JP6732257B2

  • Multi-color laminated dental mill blank

    WO2018074605A1